The Interior Designing of Omah Batik in Bayat - Annisa Isma; Joko Budiwiyanto (Pendhapa, 2020)
The interior Designing of Omah Batik in Bayat is aimed at accommodating the activities of developing traditional batik, especially in Bayat by presenting the theme of several motifs on batik which are packaged in art deco style. This design offers facilities such as galleries, shops, vehicle repair shops, cafes, and lobbies. This goal is achieved by a design method that uses a design process including input, synthesis, and output. The input is in the form of literature, field data, and synthesis through the design analysis process; whereas the output is in the design results. The approach used is the approach to function, ergonomics, themes, and styles as well as materials. The design analysis takes ideas from several batik motifs, such as kawung, sidomukti, and parang motifs combined with art deco patterns. The design result is the interior design of Omah Batik in Bayat which has several main facilities such as a lobby, shop, gallery, café, and vehicle repair shop. Supporting facilities include inns, audio-visual rooms, and a library in art deco style.